Catalytic ozonation oxidation of ketoprofen by peanut shell-based biochar effects of the pyrolysis temperatures - Li, Haiquan (Environmental technology, 2022)
A series of peanut shell (HS)-based biochar were prepared at different pyrolysis temperatures and subsequently used as the effective ozonation catalysts for ketoprofen (KET) degradation in aqueous solution. The physicochemical properties and morphology of the obtained biochar were analysed by ICP, TG, XRD, FT-IR, SEM, TEM, BET and etc. characterizations. The results demonstrated that the pyrolysis temperature played an important role on the structure and morphology of HS-based biochar. As the pyrolysis temperature increased, the cellulose and hemicellulose of HS gradually decomposed, resulting in the loss of biochar mass, improvement of the surface roughness, the increase of specific surface area, and the formation of new functional groups. The HS-based biochar pyrolyzed at 600°C (HS600) achieved the fast KET degradation rate with the pseudo-first-order rate constant of 0.922 min-1 and the low adsorption rate of 1.3% in O3/HS600 process. Meanwhile, the effects of the HS600 dosage, initial KET concentration, temperature, water matrix, and solution pH on KET degradation were systematically evaluated. Besides, the HS600 displayed great stability and reusability towards KET degradation during multiple cycling experiments. Moreover, the single oxygen, superoxide radical and hydroxyl radical were involved in O3/HS600 process and the mechanisms for the improvement of KET degradation were also elucidated. It could be speculated that the enhancement of the catalytic ozonation by HS-based biochar was probably attributed to the increased active sites and the intense chemical bonds, and delocalized π electron